Pressure inductive head of bag-in-box filling machine - ZHU DEJIN (2015)
The invention discloses a pressure inductive head of a bag-in-box filling machine. The pressure inductive head comprises an inductive head body. An inductive face is arranged on the inductive head body. A plurality of plastic bag attaching bodies are arranged on the inductive face. A first pressure sensitive contact and a second pressure sensitive contact are arranged on the inductive face. A sticking layer is arranged on the surface of each plastic bag attaching body. The number of the plastic bag attaching bodies is not smaller than 4. Due to the fact that the inductive face is arranged on the body of the pressure inductive head of the bag-in-box filling machine, the multiple plastic bag attaching bodies are arranged on the inductive face, and the inductive face can be more tightly attached to plastic bags through the attaching bodies, the two pressure sensitive contacts on the inductive face can more accurately induce pressure generated in filled objects inside the plastic bags, and the sensitivity of the pressure inductive head of the bag-in-box filling machine is greatly improved.